2015
DOI: 10.1007/s00417-015-2980-8
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the ISNT and IST rules on retinal nerve fiber layer measurement on spectral-domain optical coherence tomography in normal Indian children

Abstract: The ISNT and the IST rules for RNFL are not universally followed by all normal eyes in children. All deviations should therefore not be considered pathological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…The average RNFL thickness in our study was determined 94.46 ± 8.70 μm which is consistent with findings reported in the literature. [ 2 3 4 5 6 7 8 9 10 ] Table 6 shows OCT values of the previous studies of pediatric population with Cirrus HD-OCT, interocular symmetry and our present study as well. [ 21 22 23 24 25 26 27 28 29 ]…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The average RNFL thickness in our study was determined 94.46 ± 8.70 μm which is consistent with findings reported in the literature. [ 2 3 4 5 6 7 8 9 10 ] Table 6 shows OCT values of the previous studies of pediatric population with Cirrus HD-OCT, interocular symmetry and our present study as well. [ 21 22 23 24 25 26 27 28 29 ]…”
Section: Discussionmentioning
confidence: 69%
“…found that ISNT rule on the RNFL in an Indian population was followed only by 30 eyes (23.8%), while the IST (inferior thickest followed by superior and temporal) rule was followed by 66 eyes (52.4%) ( P < 0.001). [ 4 ] Rao et al . found the RNFL to be thickest in the superior, inferior, nasal, and temporal quadrants in an Indian pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations